Level of Critical Thinking Abilities of Madrasah Aliyah Negeri 1 Jombang Students in Solving Geometry Problems: A Review Based on Cognitive Style - Zain, Nurmalia Khoirunisa; Marhayati, Marhayati (Universitas Islam Sultan Agung, 2024)
Critical thinking ability is the skill level of complex thinking individuals use to solve problems. This study aimed to describe the critical thinking ability of Madrasah Aliyah students with their respective cognitive styles, namely verbalizer and visualizer, in solving geometric transformation problems. This study uses a descriptive qualitative approach with a case study type. The research subjects were selected by purposive sampling, with one student each using a verbalizer and visualizer cognitive style. The data collection techniques used were tests and interviews. The data validity test used in this study was technical triangulation, which was then analyzed by data reduction, data presentation, and conclusion. The results showed that students with a verbalizer cognitive style had level 5 critical thinking ability, namely, advanced thinkers, characterized by students being able to explain strategies coherently and guess alternative solutions but not yet able to explain them. Meanwhile, students with a visualizer cognitive style have level 4 critical thinking ability, namely The practising thinker, characterized by students being able to solve problems but not yet being able to explain what is being done and not knowing the alternative solutions that can be used.Keywords: Critical Thinking Levels, Problem Solving, Verbalizer-Visualizer Cognitive Style